2007
DOI: 10.1634/theoncologist.12-11-1361
|View full text |Cite
|
Sign up to set email alerts
|

The NCCN Clinical Practice Guidelines on Venous Thromboembolic Disease: Strategies for Improving VTE Prophylaxis in Hospitalized Cancer Patients

Abstract: After completing this course, the reader will be able to:1. Discuss the importance of thromboprophylaxis in hospitalized cancer patients.2. Identify risk factors for cancer-associated thrombosis.3. Identify strategies to improve compliance with prophylaxis recommended by NCCN guidelines.Access and take the CME test online and receive 1 AMA PRA Category 1 Credit ™ at CME.TheOncologist.com CME CME ABSTRACTThe risk for venous thromboembolism (VTE) is high in hospitalized cancer patients, and is associated with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 62 publications
(88 reference statements)
4
54
0
5
Order By: Relevance
“…Although VTE is a preventable cause of death [19], it remains the leading cause of death in patients with overt malignancy [20], second only to the cancer diagnosis. VTE is the most common cause of 30-day mortality among patients with cancer who undergo surgery [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although VTE is a preventable cause of death [19], it remains the leading cause of death in patients with overt malignancy [20], second only to the cancer diagnosis. VTE is the most common cause of 30-day mortality among patients with cancer who undergo surgery [21].…”
Section: Introductionmentioning
confidence: 99%
“…A administração de enoxaparina por quatro semanas reduziu significativamente a incidência de TEV na quarta semana após a operação confirmada por venografia (4,8% vs. 12%). Segundo o National Comprehensive Cancer Network (NCCN), o uso deve ser mantido por quatro semanas, na dose de 40 mg ao dia, no pós-operatório 6 . Apesar da reconhecida importância, a tromboprofilaxia é sistematicamente subutilizada nos hospitais, como exposto em estudo retrospectivo americano em pacientes de risco para TEV.…”
Section: Figura 3 Tomografia Com Emissão De Positrons Com Implante Punclassified
“…Apesar da reconhecida importância, a tromboprofilaxia é sistematicamente subutilizada nos hospitais, como exposto em estudo retrospectivo americano em pacientes de risco para TEV. Esse revelou taxas de profilaxia de apenas 25%, mesmo nos pacientes oncológicos 6 . Essa profilaxia inadequada tem consequên-cias graves e tem sido revista.…”
Section: Figura 3 Tomografia Com Emissão De Positrons Com Implante Punclassified
“…New treatment guidelines from the National Comprehensive Cancer Network (NCCN) and American Society of Clinical Oncology (ASCO) accept prophylaxis for VTE in hospitalized cancer patients in the absence of major bleeding or other contraindications to anticoagulants [50,61]. Contraindications to anticoagulation according to ASCO guidelines include uncontrollable bleeding, active cerebrovascular hemorrhage, dissecting or cerebral aneurysm, bacterial endocarditis, active peptic or other gastrointestinal ulceration, severe uncontrolled or malignant hypertension, severe head trauma, pregnancy (warfarin), heparin-induced thrombocytopenia and epidural catheter placement.…”
Section: Prevention and Treatment Of Venous Thromboembolism In Cancermentioning
confidence: 99%
“…Low-molecular-weight heparin, dalteparin 5000 units s.c daily, enoxaparin 40 mg s.c daily or fondaparinux 2.5 mg s.c daily is recommended for prophylaxis of VTE in patients with cancer [50,61,62]. A randomized clinical trial of combination chemotherapy with LMWH with dalteparin 5000 units once daily for 18 weeks compared to chemotherapy alone in patients with small-cell lung cancer revealed that combination therapy with dalteparin increased disease-free survival (10 months) compared chemotherapy alone (6 months, P=0.01) [63].…”
Section: Prevention and Treatment Of Venous Thromboembolism In Cancermentioning
confidence: 99%